Catalytic hydroconversion of Yiwu lignite over solid superacid and solid superbase. (15th February 2019) - Liu, Zhong-Qiu; Wei, Xian-Yong; Liu, Fang-Jing; Liu, Guang-Hui; Zong, Zhi-Min
Highlights: TFMSA/AP and Mg2 Si/γ-Al2 O3 were facilely prepared by impregnating TFMSA onto AP and Mg2 Si onto γ-Al2 O3 . TFMSA/AP is highly active for hydrocracking Car –Calk and Calk –O bridged bonds in YLER, DNM, and BOB. Arenes are the main compounds from hydrocracking Car –Calk and Calk –O bridged bonds in YLER . Mg2 Si/γ-Al2 O3 is highly active for hydrocracking Car –O and Calk –O bridged bonds in YLER, ODB, and BOB. Arenols are the main compounds from hydrocracking Car –O and Calk –O bridged bonds in YLER . Abstract: Trifluoromethanesulfonic acid supported on attapulgite powder (TFMSA/AP) and Mg2 Si/γ-Al2 O3 were facilely prepared by impregnating TFMSA onto AP and Mg2 Si onto γ-Al2 O3 . The extraction residue from Yiwu lignite (YLER ) was subjected to non-catalytic hydroconversion (NCHC) and catalytic hydroconversion (CHC) over TFMSA/AP and Mg2 Si/γ-Al2 O3, respectively. Detailed molecular compositions of the soluble portions from the NCHC (SPNCHC ) and CHC over TFMSA/AP (SPCHC-A ) and Mg2 Si/γ-Al2 O3 (SPCHC-B ) were characterized with a gas chromatograph/mass spectrometer. As a result, the yields of SPCHC-A and SPCHC-B are 19.6% and 17.5%, respectively, which are much higher than that of SPNCHC (1.04%), suggesting that both TFMSA/AP and Mg2 Si/γ-Al2 O3 show excellent activity for the CHC of YLER . Arenes and arenols are predominant in SPCHC-A and SPCHC-B, respectively, while large amounts of alkanoates were detected in SPNCHC . The results indicate that TFMSA/AP effectively catalyzes the cleavage of Car –Calk and Calk –O bridged bonds (BBs) in YLER, while Mg2 Si/γ-Al2 O3 significantly promotes the cleavage of C–O BBs in YLER . Di(1-naphthyl)methane, 1-methylnaphthalene, oxydibenzene, and benzyloxybenzene were used as coal-related model compounds (CRMCs) for the CHC to further explore the catalysis of TFMSA/AP and Mg2 Si/γ-Al2 O3 . The results show that TFMSA/AP not only releases mobile H + but also heterolytically splits H2 to form an immobile H − and a mobile H +, leading to the cleavage of Calk –Car and Calk –O BBs in the CRMCs. In contrast, Mg2 Si/γ-Al2 O3 facilitates heterolytically splitting H2 to an immobile H + and a mobile H −, resulting in the cleavage of C–O BBs in the CRMCs.